ANALISIS MODEL EVALUASI PEMBELAJARAN YANG EFEKTIF UNTUK SISWA MI/SD - Cindy Alya Maharani Cindy; Katni Katni (Universitas Muhammadiyah Ponorogo, 2022)
This study aims to analyze effective learning evaluation models for MI/SD students. The research method uses a qualitative approach with document analysis and literature studies on evaluation theories and learning practices in elementary schools relevant to this study. The results of the analysis indicate that an effective evaluation model for MI/SD students is an evaluation that is continuous, authentic, contextual, and able to assess the learning process and outcomes holistically. Formative evaluation has been proven to be able to help teachers monitor learning progress in real time, while authentic evaluation and portfolios provide a real picture of student abilities in relevant learning situations. This study concludes that the combination of various evaluation models with adjustments to the needs, basic competencies, and characteristics of students can improve the quality of learning and encourage the achievement of optimal learning outcomes.